The annual reproductive cycle and sex inversion of the Picnic seabream, Acanthopagrus berda (Forsskål 1775) from Indian waters: Histological and morphometric description. (11th July 2019) - Madathampady Thomas, Shilta; Padinhate Purayil, Suresh Babu; Narinder Kumar, Chadha; Pillaru Kandiyil, Asokan; Kavungal, Vinod; Joseph, Imelda; Banerjee Sawant, Paramita; Abhijith, Ramya
Abstract: The annual reproductive cycle of picnic seabream, Acanthopagrus berda (Forsskål, 1775), one of the potential aquaculture candidate from estuarine waters of Calicut, Kerala (India) was studied. Based on the morphological and histological studies, the ovotestes of A. berda were classified as active male, active female, inactive male, inactive female, transitional and undifferentiated. Histological observation of transitional gonads showed signs of degeneration in the testicular lobe, proliferation of connective tissue and empty sperm ducts indicating protandrous hermaphroditism in A. berda . Ovary was classified into seven maturity stages (virgin, developing virgin, developing, maturing, mature, running, spent) and testis into five maturity stages (resting, maturing, mature, running, spent). Gonadal development in A. berda indicated resting phase (February–July), pre‐spawning phase (March–August) and spawning phase (August–December). Inactive (24.6%) and active males (21.6%) were observed as dominant in smaller length classes (140–250 mm TL), whereas inactive (18%) and active females (51%) were observed as dominant in larger length classes (251–450 mm TL). Few primary females (28.1%) were observed in smaller (below 250 mm TL) and few primary males (28.5%) were observed in larger length classes (above 250 mm TL). From the present study, it can be concluded that in A. berda, most of the individuals function first as males and then change sex to female, but few continue to function as either male or female throughout their lifespan indicating digynous protandrous hermaphroditism.